Modulation of oxidative stability of haemoglobin inside liposome-encapsulated haemoglobin. (11th December 2012) - Awasthi, Vibhudutta; Yadav, Vivek R.; Goins, Beth; Phillips, William T.
Abstract : The major hurdle in the formulation of liposome-encapsulated haemoglobin (LEH) is the oxidation of haemoglobin (Hb) into methaemoglobin during storage and after administration. In order to reduce this oxidative degradation, we tested various reducing conditions in the presence of catalase. We found that at 37°C more than 50% of Hb oxidized to methaemoglobin within 24 h, whereas in presence of catalase, the oxidation was significantly reduced. The effect of catalase was further enhanced by a reduction mixture containing β-NAD, d-glucose, adenine, inosine, MgCl2, KCl, KH2 PO4 and Na2 HPO4 ; only 14% methaemoglobin was generated in the presence of catalase and reduction mixture. Contrary to the expectation, glutathione, deferoxamine and homocysteine enhanced Hb oxidation. The presence of CRM inside liposomes (250 nm) significantly decreased Hb oxidation. The results suggest that catalase and a well-defined mixture of co-factors may help control Hb oxidation for improvement in the functional life of LEH.